Given that f(x) = 3x - 7 and that (f + g)(x) = 7x + 3, find g(x).

facas9 2021-09-30 Answered
Given that f(x) = 3x - 7 and that (f + g)(x) = 7x + 3, find g(x).

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Plainmath recommends

  • Ask your own question for free.
  • Get a detailed answer even on the hardest topics.
  • Ask an expert for a step-by-step guidance to learn to do it yourself.
Ask Question

Expert Answer

casincal
Answered 2021-10-01 Author has 9744 answers
Recall that (f+g)(x)=f(x)+g(x) so we can write: 7x+3=(3x-7)+g(x)
Subtract 3x from both sides: 4x+3=-7+g(x)
Add 7 to both sides: 4x+10=g(x)
or
g(x)=4x+10
Have a similar question?
Ask An Expert
18
 

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Relevant Questions

asked 2021-06-22

Given that \(f(x) = 3x - 7\) and that \((f + g)(x) = 7x + 3\), find g(x).

asked 2021-09-21
\(\displaystyle{f}:{R}\to{R}\)
f(x)=7x-3
Prove that f is onto.
asked 2021-09-23
Find domain of fog, if
1. \(\displaystyle{f{{\left({x}\right)}}}={x}+{5};{g{{\left({x}\right)}}}=\frac{{7}}{{{x}+{7}}}\)
2. \(\displaystyle{f{{\left({x}\right)}}}=\sqrt{{x}};{g{{\left({x}\right)}}}={6}{x}+{18}\)
asked 2021-09-10

\(\displaystyle{f}:{R}\to{R}\)
\(f(x)=7x-3\)
Prove that f is onto.

asked 2021-06-16

g is related to one of the parent functions. Describe the sequence of transformations from f to g. \(g(x) = x^3 + 7\)

asked 2021-05-14
Describe the transformations of \(\displaystyle{f{{\left({x}\right)}}}=\sqrt{{t}}{x}\) that result in the functions listed below.
\(\displaystyle{g{{\left({x}\right)}}}=-\sqrt{{x}}+{2}\)
\(\displaystyle{h}{\left({x}\right)}={\left(\sqrt{{x}}-{3}\right)}+{4}\)
asked 2021-09-16

Tabular representations for the functions f, g, and h are given below. Write g(x) and h(x) as transformations of f(x).

\(\begin{array}{|c|c|c|c|c|c|} \hline x & -2 & -1 & 0 & 1 & 2 \\ \hline \hline f(x) & -2 & -1 & -3 & 1 & 2 \\ \hline \end{array}\)

\(\begin{array}{|c|c|c|c|c|c|} \hline x & -1 & 0 & 1 & 2 & 3 \\ \hline g(x) & -2 & -1 & -3 & 1 & 2 \\ \hline \end{array}\)

\(\begin{array}{|c|c|c|c|c|c|} \hline x & -2 & -1 & 0 & 1 & 2 \\ \hline h(x) & -1 & 0 & -2 & 2 & 3 \\ \hline \end{array}\)

...